UPAYA MENJAGA KELANGSUNGAN USAHA KOPERASI DENGAN INTERNAL CONTROL BERDASARKAN COSO FRAMEWORK - Dinda Aulia; Novita (RELEVAN : Jurnal Riset Akuntansi, 2021)
Cooperative collated with the aim to promote the welfare of its members in particular and society in its general and helped build the structure of the national economy to realize an advanced society fair and prosperous based on Pancasila UUD 1945 section 33. With this statement, this study aims to decide the Internal Control System of the COSO Framework of the Primary Kartika Cipta Wira Yudha Cooperative and the influence of the Internal Control System on going concern. The research was conducted by distributing questionnaires where the research sample used purposive sampling method and then obtained 75 active participatory cooperative members. This study uses SmartPLS. The results showed that the COSO Framework Internal Control System had a positive and significant effect on the going concern of the cooperative's. From the results of the study, it can be interpreted that Primary Koperasi Kartika Cipta Wira Yudha has carried out a control environment, risk assessment, control activities, information and communication, and monitoring properly. The implementation of an internal control system is considered very important to improve cooperatives, by taking into account the five components of the internal control system to improve going concern.